IMPACT OF SPRAYING A NUTRIENT SOLUTION ON SOME EGGPLANT GENOTYPES UNDER PROTECTED CULTIVATION - H. A. Addai; M. M. Al-Abdaly; S. A. Mahmood (مجلة الأنبار للعلوم الزراعية)
This study investigated the response of several genotypes of eggplant under protected agriculture to different levels of spraying with nutrient solutions. The study involved spraying five hybrid eggplants, namely Barcelona, ​​Emerald, E35, E21, and E53 with the Brexil Dou nutrient solution at three levels of 0, 2.5, and 5 gm L-1. The treatments were distributed in a factorial experiment within a completely randomized block design (CRBD) with three replications. The Barcelona hybrid excelled in most of the growth traits and yields attaining the highest values ​​for the number of branches and leaves. It also achieved the highest number of fruits as well as yield per plant at 5.15 branches plant-1, 63.34 leaves plant-1, 20.77 fruits plant- 1, and 2.650 kg plant-1, respectively, while the E21 registered the lowest values ​​for the same traits. The 5 gm l-1 nutrient solution concentration produced the highest values ​​for the number of branches 5.71 plant branches-1, leaves 59.71 plant leaves-1, fruits per plant 19.68 plant fruits-1, and plant yield 2.432 kg compared to the control which had the lowest values.